The storm whale - Davies, Benji (New York : Henry Holt and Company, 2014)
"Every day, in a house by the sea, a little boy watches his father leave for a long day's work. One night, a great storm washes a small whale onto the beach. The boy discovers the whale is a good listener. The father discovers the boy is lonely. Together, they return the whale to the sea. And from that day on, the boy learns that the father can be a good listener too"--
"First published in hardcover in 2013 by Simon & Schuster UK ."
Keywords: Whales -- Fiction; Fathers and sons -- Fiction; Loneliness -- Fiction; JUVENILE FICTION / Family / Parents; JUVENILE FICTION / Animals / Mammals